CpG Oligodeoxynucleotides Modulate Innate and Adaptive Functions of IgM+ B Cells in Rainbow Trout - Simón, Rocío; Díaz-Rosales, Patricia; Morel, Esther; Martín, Diana; Granja, Aitor G.; Tafalla, Carolina (Frontiers in Immunology, 2019)
Oligodeoxynucleotides (ODN) containing unmethylated CpG motifs have been widely postulated as vaccine adjuvants both in mammals and teleost fish. However, to date, the effects that CpGs provoke on cells of the adaptive immune system remain mostly unexplored in fish. Given that rainbow trout (Oncorhynchus mykiss) IgM+ B cells from spleen and blood transcribe high levels of toll like receptor 9 (TLR9), the receptor responsible for CpG detection in mammals, in the current work, we have investigated the effects of CpGs on both spleen and blood IgM+ B cells from this species. CpGs were shown to exert strong proliferative effects on both spleen and blood IgM+ B cells, also increasing their survival. The fact that CpGs increase the size of IgM+ B cells, reduce the expression of surface IgM and IgD and up-regulate the number of IgM-secreting cells strongly suggest that IgM+ B cells differentiate to plasmablasts / plasma cells in response to CpG stimulation. Additionally, CpGs were shown to modulate the antigen presenting capacities of trout IgM+ B cells through an increased surface MHC II expression and transcriptional up-regulation of co-stimulatory molecules, although in this case, significant differences were observed between the effects exerted on spleen and blood cells. Similarly, differences were observed between spleen and blood IgM+ B cells when CpG stimulation was combined with B cell receptor (BCR) cross-linking. Finally, CpGs were also shown to affect innate functions of teleost IgM+ B cells such as their phagocytic capacity. These results demonstrate that CpGs regulate many adaptive and innate functions of teleost B cells, supporting their inclusion as adjuvants in novel vaccine formulations.